2002
DOI: 10.1021/jp012516q
|View full text |Cite
|
Sign up to set email alerts
|

Empirical Formula of Exciton Coherent Domain in Oligomers and Application to LH2

Abstract: We investigated the mechanism by which the length of exciton coherent domain in the linear array of pigments is determined. Correctly solving a generalized master equation with memory function obtained by the secondorder perturbation of the intermolecular interaction, we obtained an empirical formula for the length of exciton coherent domain, abbreviated as coherence length. In the absence of inhomogeneity, this coherence length is expressed by a linear function of the ratio between the intermolecular coupling… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
33
1

Year Published

2003
2003
2009
2009

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(35 citation statements)
references
References 40 publications
1
33
1
Order By: Relevance
“…An empirical law for the coherence length for a Frenkel exciton system has been suggested. 23,34 The absorption spectrum reflects the solute/solvent configuration of the system while the molecule resides in the ground state, whereas the emission spectrum reflects the configuration of the system while the molecule resides in the excited state. The difference in solute/solvent configuration is manifested in the Stokes shift.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…An empirical law for the coherence length for a Frenkel exciton system has been suggested. 23,34 The absorption spectrum reflects the solute/solvent configuration of the system while the molecule resides in the ground state, whereas the emission spectrum reflects the configuration of the system while the molecule resides in the excited state. The difference in solute/solvent configuration is manifested in the Stokes shift.…”
Section: Discussionmentioning
confidence: 99%
“…The energy level structure of the donor and acceptor plays a key role in the energy transfer. The nature of the donor exciton state ͑coherence length͒, which depends on the coupling strength between the chromophore units within the array relative to the fluctuation in transition frequency due to the solvent and conformational disorder, 23,34 is also a critical factor that governs the energy transfer. To this end, in addition to the fluorescence time profile at fixed detection wavelengths, we have measured TRF spectra over the entire emission region of the donor and acceptor to elucidate the energy structures and the dynamics occurring in the porphyrin arrays.…”
Section: Introductionmentioning
confidence: 99%
“…According to the empirical formula for one-dimensional linear arrays developed by Kakitani et al, the coherence length N c can be estimated by Equation (4). [38,39] N c 1.…”
mentioning
confidence: 99%
“…This excitonic delocalization in light-harvesting systems is determined from the interpigment coupling strength (constructive factor) and line-broadening effects such as electron ± phonon coupling and site inhomogeneity (destructive factor). [38] Numerous theoretical and experimental methods have been utilized to assess the extent of exciton delocalization in LH2. These studies demonstrated that the coherence length of the strongly coupled B850 ring in LH2 is about four Bchl a molecules.…”
mentioning
confidence: 99%
See 1 more Smart Citation